2019
DOI: 10.1002/eap.1920
|View full text |Cite
|
Sign up to set email alerts
|

Fate of atmospherically deposited NH4+ and NO3 in two temperate forests in China: temporal pattern and redistribution

Abstract: The impacts of anthropogenic nitrogen (N) deposition on forest ecosystems depend in large part on its fate. However, our understanding of the fates of different forms of deposited N as well as the redistribution over time within different ecosystems is limited. In this study, we used the 15N‐tracer method to investigate both the short‐term (1 week to 3 months) and long‐term (1–3 yr) fates of deposited NH4+ or NO3− by following the recovery of the 15N in different ecosystem compartments in a larch plantation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 72 publications
4
15
1
2
Order By: Relevance
“…The 15 N tracer method is the only approach currently available to trace and quantify the fate and (re)distribution of deposited N over multiyear periods in forest ecosystems (Nadelhoffer et al, 1999; Templer et al, 2012). Many studies have examined the fate of various forms of 15 N added to forest ecosystems (Feng et al, 2008; Goodale, 2017; Gurmesa et al, 2016; Li et al, 2019; Liu, Peng, et al, 2017; Liu, Yu, et al, 2017; Templer et al, 2012; Wang et al, 2018). Most of these, largely located in temperate and boreal forests (see Templer et al, 2012), showed most added 15 N ending up in the organic soil (Feng et al, 2008; Goodale, 2017; Li et al, 2019; Liu, Peng, et al, 2017; Templer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The 15 N tracer method is the only approach currently available to trace and quantify the fate and (re)distribution of deposited N over multiyear periods in forest ecosystems (Nadelhoffer et al, 1999; Templer et al, 2012). Many studies have examined the fate of various forms of 15 N added to forest ecosystems (Feng et al, 2008; Goodale, 2017; Gurmesa et al, 2016; Li et al, 2019; Liu, Peng, et al, 2017; Liu, Yu, et al, 2017; Templer et al, 2012; Wang et al, 2018). Most of these, largely located in temperate and boreal forests (see Templer et al, 2012), showed most added 15 N ending up in the organic soil (Feng et al, 2008; Goodale, 2017; Li et al, 2019; Liu, Peng, et al, 2017; Templer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the fate of various forms of 15 N added to forest ecosystems (Feng et al, 2008; Goodale, 2017; Gurmesa et al, 2016; Li et al, 2019; Liu, Peng, et al, 2017; Liu, Yu, et al, 2017; Templer et al, 2012; Wang et al, 2018). Most of these, largely located in temperate and boreal forests (see Templer et al, 2012), showed most added 15 N ending up in the organic soil (Feng et al, 2008; Goodale, 2017; Li et al, 2019; Liu, Peng, et al, 2017; Templer et al, 2012). But few temperate studies traced the distribution of deposited N for more than 2 years (Goodale, 2017; Krause et al, 2012; Li et al, 2019; Nadelhoffer et al, 2004; Preston & Mead, 1994; Wessel et al, 2013), and the three 15 N tracer studies in tropical and subtropical forests suggest instead that plants and mineral soil sinks are more important (Gurmesa et al, 2016; Liu, Yu, et al, 2017; Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations